A new species of Pterodectes Robin, 1877 (Proctophyllodidae: Pterodectinae) from the pale-breasted thrush, Turdus leucomelas (Passeriformes: Turdidae) - Hernandes, Fábio A. [UNESP]; Valim, Michel P. (My University, 2005)
A new species of feather mite, Pterodectes fissuratus sp. n., is described from the pale-breasted thrush, Turdus leucomelas Veillot (Passeriformes: Turdidae), in Brazil. This species is easily distinguished by having numerous well-pronounced lacunae and a longitudinal median furrow on prodorsal and hysteronotal shields in both sexes. Copyright © 2005 Magnolia Press.
Keywords: Analgoidea; Astigmata; Brazil; Feather mite; Systematics; Acari; Passeri; Passeriformes; Proctophyllodidae; Turdidae; Turdus leucomelas